(untitled) (Revue D’études Interculturelles De L’image, 2018)
Abstract | This essay investigates the collaboration between McLuhan and the Romanian born Canadian artist, Sorel Etrog. In 1975, Etrog’s movie Spiral was shown at the Centre for Culture and Technology, established by McLuhan at the University of Toronto. Following that event, McLuhan suggested that Etrog select “stills from the film so that he could provide an annotation to those images – a free form text of quotations from various writers – as well as a commentary”. Thanks to another great protagonist of the Canadian cultural scene, Barry Callaghan, that idea became a tangible object a few years after McLuhan had passed away: Spiral. Images from the film. Text by Marshall McLuhan, was in fact published in 1987 by Exile Editions in Toronto. Today, it remains as a memento of an original artistic encounter. It also remains as a tool to reconsider our environment through poetry and images, as words and still-shots are cast to pose an intellectual challenge to an increasingly materialistic society. As a book, Spiral is conceived to make ideas on media and society resonate through a witty juxtaposition of images from the film and literary quotations from a broad Western tradition that encourages readers to navigate the ongoing profound cultural shift. Known but not often investigated when discussing McLuhan’s artistic associations, the collaboration between Etrog and McLuhan ought to be delved into for different reasons. It is, in fact, strategic to appreciate how McLuhan has acted as a facilitator of a renewed 20th century inter-art dialogue. Then, it helps to consider the conscious shift from modernist avant-garde to new avant-gardes and art forms of the 1970s in relation to McLuhan’s environmental explorations. Finally, it also pays homage to an artist that deserves to be remembered as one of the most original voices of the Canadian artistic renaissance. Résumé | Cet essai étudie la collaboration entre McLuhan et l’artiste canadien d’origine roumaine, Sorel Etrog. En 1975, le film Spiral d’Etrog a été présenté au Centre for Culture and Technology, créé par McLuhan à l’Université de Toronto. En réponse à cet événement, McLuhan a suggéré qu’Etrog sélectionne « des images du film pour qu’il puisse leur fournir une annotation – un texte libre de citations de divers auteurs – ainsi qu’un commentaire ». Grâce à un autre grand protagoniste de la scène culturelle canadienne, Barry Callaghan, cette idée devint un objet tangible quelques années après la mort de McLuhan : Spiral. Images from the film. Text by Marshall McLuhan fut publié en 1987 par Exile Editions à Toronto. Aujourd’hui, il demeure un souvenir d’une rencontre artistique originale. Il demeure également un outil pour reconsidérer notre environnement à travers la poésie et les images, alors que les mots et les images fixes sont jetés pour poser un défi intellectuel à une société de plus en plus matérialiste. Comme livre, Spiral est conçu pour faire résonner des idées sur les médias et la société par une juxtaposition spirituelle d’images du film et des citations littéraires d’une large tradition occidentale qui encourage les lecteurs à naviguer dans le profond changement culturel en cours. Connue, mais rarement étudiée lors des discussions sur les associations artistiques de McLuhan, la collaboration entre Etrog et McLuhan devrait être explorée pour différentes raisons. Il est, en fait, stratégique d’apprécier comment McLuhan a agi en tant que facilitateur d’un dialogue interartistique du 20e siècle renouvelé. Ensuite, il est utile de considérer le passage conscient de l’avant-garde moderniste à de nouvelles formes avant-gardistes et artistiques des années 1970 en relation avec les explorations environnementales de McLuhan. Enfin, cela rend également hommage à un artiste qui mérite qu’on se souvienne de lui comme l’une des voix les plus originales de la renaissance artistique canadienne.